Ex vivo-expanded human CD19+TIM-1+ regulatory B cells suppress immune responses in vivo and are dependent upon the TIM-1/STAT3 axis - Shankar, S; Stolp, J; Juvet, SC; Beckett, J; Macklin, PS; Issa, F; Hester, J; Wood, KJ (Springer Nature, 2022)
Regulatory B cells (Breg) are a heterogenous population with immune-modulating functions. The rarity of human IL-10+ Breg makes translational studies difficult. Here we report ex vivo expansion of human B cells with in vivo regulatory function (expBreg). CD154-stimulation of human CD19+ B cells drives >900-fold expansion of IL-10+ B cells that is maintained in culture for 14 days. Whilst expBreg-mediated suppressive function is partially dependent on IL-10 expression, CRISPR-mediated gene deletions demonstrate predominant roles for TIM-1 and CD154. TIM-1 regulates STAT3 signalling and modulates downstream suppressive function. In a clinically relevant humanised mouse model of skin transplantation, expBreg prolongs human allograft survival. Meanwhile, CD19+CD73-CD25+CD71+TIM-1+CD154+ Breg cells are enriched in the peripheral blood of human donors with cutaneous squamous cell carcinoma (SCC). TIM-1+ and pSTAT3+ B cells are also identified in B cell clusters within histological sections of human cutaneous SCC tumours. Our findings thus provide insights on Breg homoeostasis and present possible targets for Breg-related therapies.